2023
DOI: 10.3390/genes14020290
|View full text |Cite
|
Sign up to set email alerts
|

DNA Double-Strand Break-Related Competitive Endogenous RNA Network of Noncoding RNA in Bovine Cumulus Cells

Abstract: (1) Background: DNA double strand breaks (DSBs) are the most serious form of DNA damage that affects oocyte maturation and the physiological state of follicles and ovaries. Non-coding RNAs (ncRNAs) play a crucial role in DNA damage and repair. This study aims to analyze and establish the network of ncRNAs when DSB occurs and provide new ideas for next research on the mechanism of cumulus DSB. (2) Methods: Bovine cumulus cells (CCs) were treated with bleomycin (BLM) to construct a DSB model. We detected the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 93 publications
0
1
0
Order By: Relevance
“…The dual luciferase reporter assay showed that miR-302d mimics remarkably inhibited the expression of CDKN1A WT (Figure 3e). opposite to the trend of CDKN1A expression (Figure 1b) and was also in agreement with the results of earlier studies [24]. Transfection of bovine cumulus cells with miR-302d mimics enhanced miR-302d expression and significantly diminished CDKN1A expression (p < 0.01, Figure 3c,d).…”
Section: Mir-302d Targeted Binding To the Cdkn1a 3 Utr And Inhibited ...supporting
confidence: 92%
See 3 more Smart Citations
“…The dual luciferase reporter assay showed that miR-302d mimics remarkably inhibited the expression of CDKN1A WT (Figure 3e). opposite to the trend of CDKN1A expression (Figure 1b) and was also in agreement with the results of earlier studies [24]. Transfection of bovine cumulus cells with miR-302d mimics enhanced miR-302d expression and significantly diminished CDKN1A expression (p < 0.01, Figure 3c,d).…”
Section: Mir-302d Targeted Binding To the Cdkn1a 3 Utr And Inhibited ...supporting
confidence: 92%
“…TargetScan database predictions illustrate that miR-302d targets binding to the CDKN1A 3 UTR at positions 614 to 620 (Figure 3a). BLM treatment of bovine cumulus cells resulted in a significant down regulation of miR-302d expression (p < 0.01, Figure 3b), which was opposite to the trend of CDKN1A expression (Figure 1b) and was also in agreement with the results of earlier studies [24]. Transfection of bovine cumulus cells with miR-302d mimics enhanced miR-302d expression and significantly diminished CDKN1A expression (p < 0.01, Figure 3c,d).…”
Section: Mir-302d Targeted Binding To the Cdkn1a 3 Utr And Inhibited ...supporting
confidence: 90%
See 2 more Smart Citations
“…It has been reported that reactive oxygen species (ROS) causes adverse changes, such as proliferation arrest, aging, apoptosis and necrosis [ 17 ]. Recently, there were research studies pointing out that chloroquine increased ROS in ovarian cancer cell lines, causing DSBs [ 18 , 19 ]. The primary sources of ROS were mitochondria and plasma membrane [ 20 ].…”
Section: Introductionmentioning
confidence: 99%